Detection and characterization of tumor cells in bone marrow of patients with primary breast cancer - Diel, Ingo J.; Costa, Serban-Dan; Kaufmann, Manfred; Bastert, Gunther (Metastatic bone disease, 1994)
Destructive growth and metastasis characterize malignant tumors. As a rule, death results from the consequences of the metastasis. Although only isolated aspects of the metastatic process have been studied, regularities have been identified that are valid for every tumor. For example, proliferating neoplastic cells reach the basal membrane, penetrate it, and make their way into the connective tissue, where they have access to blood and lymph vessels and are carried to other organ systems. After the tumor cells or emboli are caught in the capillary network or the sinusoids of bone marrow, extravasation and renewed proliferation ensues [1]. The processes regulating these events are largely unknown. Liotta et al. [2] referred to the discordance between the regulation of tumor growth and metastasis in breast cancer, which underscores the difficulties of predicting the course of the disease.
Gesehen am 07.02.2024